Eight Motivational Forces and Voluntary Turnover: A Theoretical Synthesis with Implications for Research - Maertz, Carl P.; Griffeth, Rodger W. (Journal of Management, 2004)
In this study, we synthesize, from the attitude and turnover literatures, a framework of eight (8) distinctive motives, or “Forces”. We then illustrate how the “8 Forces” framework can be utilized by turnover researchers as clarification of reported reasons for turnover, as causal mediators of turnover predictors, and as factors related to the type of turnover decision process. Finally, we discuss further implications of this framework.